A novel treatment strategy for glioblastoma multiforme and glioma associated seizures: Increasing glutamate uptake with PPARγ agonists. Issue 1 (January 2015) - Ching, Jared; Amiridis, Stephanie; Stylli, Stanley S.; Morokoff, Andrew P.; O'Brien, Terence J.; Kaye, Andrew H.
Abstract The established role of glutamate in the pathogenesis of glioma-associated seizures (GAS) led us to investigate a novel treatment method using an established drug class, peroxisome proliferator activated receptor (PPAR) gamma agonists. Previously, sulfasalazine has been shown to prevent release of glutamate from glioma cells and prevent GAS in rodent models. However, raising protein mediated glutamate transport via excitatory amino acid transporter 2 (EAAT2) has not been investigated previously to our knowledge. PPAR gamma agonists are known to upregulate functional EAAT2 expression in astrocytes and prevent excitotoxicity caused by glutamate excess. These agents are also known to have anti-neoplastic mechanisms. Herein we discuss and review the potential mechanisms of these drugs and highlight a novel potential treatment for GAS.